Modelling verification and influence of operational patterns on tribological behaviour of wheel-rail interaction. (October 2017) - Ma, Yuewei; Markine, Valeri; Mashal, Abdul Ahad; Ren, Mingfa
Abstract: Verification of the explicit finite element (FE) model with realistic wheel-rail profiles against the CONTACT model, which has not been sufficiently discussed, is performed by comparing the resulting shear stress, slip-adhesion area, etc., obtained from the two models. The follow-up studies using the verified FE model on the influence of the varying operational patterns (such as different friction, traction, etc.) on the surface and subsurface tribological responses of wheel-rail interaction are accomplished through a series of simulations. It can be concluded that the results obtained from most of the explicit FE simulations agree reasonably well with the ones from CONTACT. Also, the increase of the friction and traction can bring the stress concentrations from the subsurface upwards to the surface. Highlights: The accuracy of finite element (FE) model with realistic wheel-rail profiles is verified against CONTACT. The integrating procedure of FE modelling verification against CONTACT is proposed. The effect of the operational patterns on the tribological behaviour of wheel-rail interaction is analysed. Material plasticity can drastically affect the surface and subsurface contact properties.